2011
DOI: 10.1007/s12371-011-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphosites and Geotourism in the Parks of the Abruzzo Region (Central Italy)

Abstract: The geomorphologic landscape of the Abruzzo region is a good example of the variety and complexity of processes and morphogenetic events in Italy. Complex Meso-Cenozoic palaeogeographies are still reflected by the main mountain chains of Abruzzo and enable both scientists and tourists to make imaginary journeys through ancient, long vanished, coral atolls and blue deep seas. Valleys of glacial origin, alluvial cones, actual soils and palaeosoils still preserve the memory of these 'by-goneworlds', with unique g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In the papers which focus on geoparks and other geotourism and geoconservation initiatives (15 papers in total) the role of geoparks in the promotion of geotourism [56], representation of geodiversity [57] and geologic time [58] as well as their contribution to socio-economic rural development [59] are investigated, and examples of geopark development based on the type of geoheritage present in the area are presented [60][61][62]. Geotourism initiatives implemented outside the geoparks are also investigated [63,64]. The study conducted by Gladfelter and Mason [65] in Yosemite National Park concluded that although geotourism projects have the potential to influence visitor patterns and congestion problems in popular national parks and can make a positive contribution to the involvement of stakeholders, they may also increase environmental impacts.…”
Section: Research Trends In Geotourism Which Have Evolved Over the Pamentioning
confidence: 99%
“…In the papers which focus on geoparks and other geotourism and geoconservation initiatives (15 papers in total) the role of geoparks in the promotion of geotourism [56], representation of geodiversity [57] and geologic time [58] as well as their contribution to socio-economic rural development [59] are investigated, and examples of geopark development based on the type of geoheritage present in the area are presented [60][61][62]. Geotourism initiatives implemented outside the geoparks are also investigated [63,64]. The study conducted by Gladfelter and Mason [65] in Yosemite National Park concluded that although geotourism projects have the potential to influence visitor patterns and congestion problems in popular national parks and can make a positive contribution to the involvement of stakeholders, they may also increase environmental impacts.…”
Section: Research Trends In Geotourism Which Have Evolved Over the Pamentioning
confidence: 99%
“…The selection of the path and the main stop sites was qualitatively based on three main criteria similar for archeology and geology: (i) location and spatial connection along the Terre Peligne area; (ii) site type and origin, and (iii) temporal distribution in the geological/archeological time scale [28,[40][41][42]. Even if at this stage we did not run a quantitative assessment of the sites [20], this approach is in agreement with what has been done in many cases for geosites evaluation (e.g., within Environmental Impact Assessment and territorial planning [11,12,43]; inventories of natural heritage sites, [31,35,40,44]; tourist promotion [14,45]; management of nature parks [4,6,22,46,47]).…”
Section: Methodsmentioning
confidence: 61%
“…The cultural heritage of Italy is one of the most noticeable in the world and is intimately related to the landscape and its long-lasting history. This is valued mainly in the major cities, popular localities, and national parks [1][2][3][4][5][6][7][8], while it is poorly developed in many minor villages, country areas, local natural reserves, and less-known areas, such as in the inner-mountain areas of the Apennines. However, there are many places, archeological sites, and landscapes that preserve the geological history of our country, as well as important stages of human history [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its roots lie in the late seventeenth and eighteenth centuries (Hose, 2016). The main focuses and goals of geotourism are (Panizza & Piacente, 1993;Reynard & Coratza, 2007;Coratza & Regolini-Bissig, 2009;Miccadei, Piacentini, & Esposito, 2011;Hose, 2016;Reynard & Brilha, 2017):…”
Section: Introductionmentioning
confidence: 99%